Physicochemical properties and storage stability of nanoencapsulated docosahexaenoic acid with different gum arabic Maillard reaction products - L. Zhou; S. Yuan; T. Chang; T. Li; J. Hao; J. Liu (Grasas y Aceites)
In this study, the polysaccharide gum arabic (GA) and proteins, including sodium caseinate (SC), soy protein isolate (SPI), and gelatin (GE) Maillard reaction products (MRPs), were used as encapsulating materials for making docosahexaenoic acid (DHA) nanoemulsions. The optimum conditions were as follows: ultrasonic power 585 W, ultrasonic time 20 min, total mass concentration 5 %, core wall ratio 1:2. Scanning electron microscope, transmission electron microscopy, and Fourier transform infrared analysis confirmed the effective encapsulation of DHA oil by the SC/GA, SPI/GA, and GE/GA MRPs, providing core protection. The thermogravimetric analysis shows that SPI/GA MRPs-DHA nanoparticles have good thermal stability. Additionally, SPI/GA MRPs-DHA nanoparticles exhibited the lowest moisture content (1.53 %) and wetting time (183 s) and the highest solubility (97.05 %), encapsulation efficiency (89.57 %), and loading capacity (44.79 %), with good oxidative and emulsion stability. This indicates that SPI/GA MRPs may be a better wall material for nanoencapsulated DHA.